Analisis Kualitas Layanan Tour Leader dalam Mendampingi Jamaah Umrah dengan Menggunakan Metode Service Quality (Studi pada PT. Bengkulu Syiar Haramain Kota Bengkulu) - Rantika Prameswari; Khairiah Elwardah; Miko Polindi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to determine the tour leader service in accompanying Umrah pilgrims at PT. Bengkulu Syiar Haramain Bengkulu City and to determine the suitability of tour leader services with five service quality indicators. The focus of the study is directed at the service aspects provided by tour leaders to Umrah pilgrims and their suitability with five service quality dimensions, namely physical evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance), and empathy (empathy). This study uses a qualitative approach with data collection methods through interviews, observations, and documentation. The results of the study indicate that the tour leader service of PT. Bengkulu Syiar Haramain is classified as good and has met the service quality standards, although there are still shortcomings in terms of reliability, namely the timeliness of distribution of Umrah pilgrim equipment, so it still requires improvement to increase pilgrim satisfaction.